Removal of Fluoride from Aqueous Solutions Using Chitosan Cryogels - Anete Jessica Arcos-Arévalo; Rosa Elvira Zavala-Arce; Pedro Ávila-Pérez; Beatriz García-Gaitán; José Luis García-Rivas; María de la Luz Jiménez-Núñez (Journal of Chemistry)
In this study, crosslinked chitosan cryogels (QE) and chitosan’s cryogels modified with iron (QEFe) were synthesized. They were characterized by BET, PZC, FTIR, and XPS spectroscopies. Results show a specific surface area of 36.67 and 29.17 m2g−1 and 7.0 and 6.1 of PZC for the cryogels QE and QEFe, respectively. FTIR results show the characteristic bands of amino and hydroxyl groups, while in the XPS analysis, interactions between iron and oxygen with fluorine were observed. The removal of fluoride at temperatures of 303, 313, and 323 K in cryogels was tested. The Ho model is the best fit for the experimental data, suggesting that there is a chemisorption process involved in the removal of fluoride. The Langmuir-Freundlich model is the best to represent the behavior of the cryogels, and it is used to sorbents with heterogeneous surfaces. A maximum fluoride adsorption capacity of 280 and 295 mg F−/g for QE and QEFe, respectively, at 303 K was obtained, showing that the removal of fluoride is favored by the iron incorporated in the polymer matrix of the cryogels. The thermodynamic parameters were obtained for both cryogels, where the values of ΔH° and ΔG° indicate that both systems are endothermic and nonspontaneous.